Expolinear model on soybean growth in Argentina and Brazil - Confalone, Adriana Elisabet; Bernardes, Marcos Silveira; Costa, Luiz Claudio; Righi, Ciro Abbud; Dourado Neto, Durval; Martin, Thomas Newton; Manfron, Paulo Augusto; Pereira, Carlos Rodrigues (Ciência Rural, 2010)
Predicting crop growth and yield with precision are one of the main concerns of the agricultural science. For these purpose mechanistic models of crop growth have been developed and tested worldwide. The feasibility of an expolinear model for crop growth was evaluated on predicting growth modification on soybean (Glycine max L. Merrill) of determined and undetermined growth cultivars, submitted to water restrictions imposed on different phenological stages. An experiment was carried out in Azul/Argentina and in Viçosa/Brazil during the growing seasons (1997/1998, 1998/1999 and 2002/2003). The expolinear model was adjusted to the dry-matter data obtained from each treatment. The model showed sensibility of Rm (maximum relative growth rate of the culture - g g-1 day-1) to variation in air temperature; of Cm (maximum growth rate of the culture - g m-2 day-1) to solar radiation and of Tb (lost time -day) to water stress. Cm values were higher without water restriction presenting, in both countries, a direct correlation with solar radiation. Without water restrictions, Rm values were lower when the average air temperature during the cycle was lower. It was observed that under water stress the culture had a bias to present higher Rm values. Tb was lower in the irrigated treatments than in those with water deficits. The analysis of the outputs clearly shows the feasibility of the expolinear model to explain the differential growth rates of soybean as a consequence of climatic conditions.

Prever o crescimento e a produtividade das culturas com precisão é uma das principais preocupações das ciências agrícolas. Com esse propósito, modelos mecanísticos de crescimento de culturas têm sido desenvolvidos e testados. A adequação do modelo expolinear de crescimento de culturas foi avaliada para prever as modificações de crescimento de cultivares de soja (Glycine max L. Merrill) de crescimento determinado e indeterminado, submetidas a déficit hídrico em diferentes estádios fenológicos. Um experimento foi conduzido em Azul/Argentina e outro em Viçosa/Brasil durante as estações de cultivo (1997/1998, 1998/1999 e 2002/2003). O modelo expolinear foi ajustado aos dados de fitomassa seca obtidos de cada tratamento. O modelo apresentou sensibilidade do parâmetro Rm (taxa máxima de crescimento relativo da cultura - g g-1 day-1) à variação na temperatura do ar; do parâmetro Cm (taxa máxima de crescimento da cultura - g m-2 day-1) à radiação solar; e do parâmetro Tb (perda em tempo - dias) ao estresse hídrico. Os valores de Cm foram maiores sem restrições hídricas, apresentando, em ambos os países, uma correlação direta com a radiação solar. Sem restrições hídricas, os valores de Rm foram menores quando a temperatura média do ar durante o ciclo foi menor. Sob estresse hídrico, a cultura mostrou uma tendência a apresentar valores de Rm maiores. Os valores de Tb foram menores nos tratamentos irrigados e maiores nos tratamentos com deficiência hídrica. A análise dos resultados mostrou claramente a capacidade do modelo expolinear para simular as diferentes taxas de crescimento da cultura da soja como uma consequência das condições climáticas.
Keywords: Water deficit; Solar radiation; Temperature; Phenological phase; Déficit hídrico; Radiação solarpt-BR; Temperatura; Fase fenológica